The beneficial of wetland Tanjung Piai to community - Mohammed Almabrouk Okashah, Ali; Hameed, Saleeh; Abdullah, Noor Aida; Khalibullah, Rafidah Banu; Mohd Yazid, Rabiatul Adawiyah (Penerbit UTHM, 2020)
Wetlands are one of the natural resources that can be seen are suffering for the past few years from human activities. The destruction of wetlands not only came from human activities but also from natural event such as continuous erosion that occurs at Tanjung Piai. The destruction of wetlands not only occurs in Malaysia but also in other country. The study was carried out at wetlands located in Tanjung Piai to identify the beneficial of wetland Tanjung Piai to community and wildlife. For the past few years, problem related to water such as flooding and water pollution worsen but wetlands seems to be one of the method to reduce these events. Wetland becomes storage area that accepts rainwater that cannot be accepted by river. Water that went through as groundwater recharge will go through filtration first thus, reducing the unwanted material in the water. Other than that wetland also acts as habitat for animals and measures to reduce erosion. Despite of the benefit of wetlands to community, wetland suffers from pollution, extinction of the mangrove and climate change. The study was carried out through observation and interview on the person in charge of the Tanjung Piai wetland. The objectives of the study are to identify the benefit of the wetland, problems that was suffered by wetland and measures to make sure wetland are in good condition.